Analisa Price to Earning Ratio (PER) dalam Pengambilan Keputusan Investasi - Muhammad Ikhsan; Arief Fahruri (Jurnal Ekonomi, 2021)
This study aims to analyze investment decisions using the Price to Earning Ratio (PER) analysis method in state-owned banking companies. The research method used is descriptive quantitative method with annualized first quarter financial report data for 2021. The results show the Price to Earning Ratio (PER) of BUMN banking stocks in that period is an average of 12.6x and based on Price to Earning Ratio analysis (PER) using the 12-month consensus share price divided by annualized net profit per share, the author makes the decision to invest in shares with a priority scale on BBTN, BBNI, BMRI and BBRI shares due to the low Price to Earning Ratio (PER) value and the potential for an increase in the next 12 months.